Resection of the ilium in patients with a sarcoma: should the pelvic ring be reconstructed?. (April 2017) - Laitinen, M. K.; Parry, M. C.; Albergo, J. I.; umathi, V. S; Jeys, L. M.; Grimer, R. J.
Abstract : Aims: The aim of the study was to investigate the controversial issue of whether the pelvic ring should be reconstructed following resection of the sarcomas of the ilium. Patients and Methods: From our database, we identified 64 patients who underwent excision of a tumour involving the ilium between 1976 and 2015. A total of 35 underwent complete resection, of whom 24 were reconstructed with a non-vascularised fibula graft, and four with extracorporeal irradiation and reimplantation. A total of 29 patients had a partial resection. The mean follow-up was 9.2 years (1.1 to 25.6). Functional outcomes were assessed using the Toronto Extremity Salvation Score (TESS) at final follow-up. In all, 32 patients (50%) had a chondrosarcoma. Results: The mean TESS for all patients was 71.6% (17% to 100%). The mean TESS for those who underwent total resection with reconstruction was 72.0% (17% to 100%) and without reconstruction it was 53.3% (20% to 90%) and for those who underwent partial resection it was 76.3% (31.3% to 100%). The rate of local recurrence was 42.2% and this was more common in those treated by partial resection (p = 0.048). The risk of local recurrence was related to the margin achieved at resection. Conclusions: Given the high rate of local recurrence following excision of a tumour from the ilium, obtaining wide surgical margins should be a priority even if this requires more aggressive surgery. In young patients, where late recurrence may occur, more radical complete resection should be considered. When total resection of the ilium is considered, reconstruction should also be considered as it confers a higher functional outcome than total resection without reconstruction. Cite this article: Bone Joint J 2017;99-B:538–43.